Analisis Perbedaan Kekuatan Struktur Kolom Akibat Tsunami pada Gedung Laboratoriom Dinas PUPR Kota Banda Aceh - Mhd. Arief Diana; Michel Kasaf; Taufik Taufik; Khairul Anwar; Deni Trianda Pitri (Yayasan Literasi Sains Indonesia, 2025)
The earthquake and subsequent tsunami that struck Banda Aceh at the end of 2004 caused extensive damage to various infrastructures, including the Laboratory Building of the Public Works Department of Banda Aceh City. This study aims to evaluate the variation in concrete strength between columns that were submerged during the tsunami and those that remained unaffected. A non-destructive testing (NDT) method was employed, using a Concrete Hammer Test device to assess the condition of the concrete. The testing was conducted on first-floor columns, with each column section tested 12 times at intervals of 3 cm between points. The results indicate a significant reduction in compressive strength, with the most severe decline observed in column K.6.4, where a 57% strength loss was recorded due to porous concrete conditions. The smallest reduction was found in columns K.1.9 and K.6.5, both showing a 5% decrease, while column K.1.7 exhibited no detectable deterioration. Overall, the majority of columns experienced notable degradation in structural integrity, underscoring the necessity for further comprehensive evaluations to determine the building’s continued feasibility and safety for use.